Burden of multimorbidity in relation to age, gender and immigrant status: a cross-sectional study based on administrative data. Issue 12 (21st December 2016) - Lenzi, Jacopo; Avaldi, Vera Maria; Rucci, Paola; Pieri, Giulia; Fantini, Maria Pia
Abstract : Objectives: Many studies have investigated multimorbidity, whose prevalence varies according to settings and data sources. However, few studies on this topic have been conducted in Italy, a country with universal healthcare and one of the most aged populations in the world. The aim of this study was to estimate the prevalence of multimorbidity in a Northern Italian region, to investigate its distribution by age, gender and citizenship and to analyse the correlations of diseases. Design: Cross-sectional study based on administrative data. Setting: Emilia-Romagna, an Italian region with ∼4.4 million inhabitants, of which almost one-fourth are aged ≥65 years. Participants: All adults residing in Emilia-Romagna on 31 December 2012. Hospitalisations, drug prescriptions and contacts with community mental health services from 2003 to 2012 were traced to identify the presence of 17 physical and 9 mental health disorders. Primary and secondary outcome measures: Descriptive analysis of differences in the prevalence of multimorbidity in relation to age, gender and citizenship. The correlations of diseases were analysed using exploratory factor analysis. Results: The study population included 622 026 men and 751 011women, with a mean age of 66.4 years. Patients with multimorbidity were 33.5% in 75 years and >60% among patients aged ≥90 years; among patients aged ≥65 years, the proportion of multimorbidity was 39.9%. After standardisation by age and gender, multimorbidity was significantly more frequent among Italian citizens than among immigrants. Factor analysis identified 5 multimorbidity patterns: (1) psychiatric disorders, (2) cardiovascular, renal, pulmonary and cerebrovascular diseases, (3) neurological diseases, (4) liver diseases, AIDS/HIV and substance abuse and (5) tumours. Conclusions: Multimorbidity was highly prevalent in Emilia-Romagna and strongly associated with age. This finding highlights the need for healthcare providers to adopt individualised care plans and ensure continuity of care.